The Effect of Transformational Leadership Style on Employee Performance Through Employee Engagement as An Intervening Variable in The Indonesian Quarantine Agency - Edi Sugiono; Suwarno Tri Widodo (International Journal of Management Science and Information Technology, 2025)
Human resources are a crucial asset for any organization, with employee performance playing a key role in achieving organizational objectives. Leadership, particularly transformational leadership, is one of the significant factors influencing employee performance as it enhances work motivation. Additionally, organizational commitment and employee engagement are essential elements that contribute to improving employee performance. Employee engagement serves as an intervening variable that mediates the relationship between transformational leadership and employee performance. The study employs a quantitative method with an associative approach to determine the relationship between these variables. Data collection was conducted using questionnaires, and the analysis was performed with SmartPLS software. The variables in this study include transformational leadership as the independent variable, employee engagement as the intervening variable, and employee performance as the dependent variable. The validity test results indicate that all items meet the required validity standards, while the reliability test results show that all variables have Cronbach's Alpha values above 0.6, indicating reliable measurements. Furthermore, transformational leadership also significantly enhances employee engagement, which, in turn, positively affects employee performance. Employee engagement is confirmed to be a mediating variable that strengthens the link between transformational leadership and employee performance. These findings align with the theory that transformational leaders can boost employee engagement by fostering an inspiring work environment, building trust, and promoting innovation.